2021
DOI: 10.37481/sjr.v4i4.382
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH LAPORAN ARUS KAS, UMUR PERUSAHAAN, DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN (Studi Empiris Perusahaan LQ45 yang terdaftar di BEI Periode 2018-2020)

Abstract: The study aims to analyze the impact the company's cash flow statements, firm age, and firm size on financial performance. The population in this study is the LQ45 company listed in the BEI 2018-2020 period. The data was analyzed using the regression panel data. Research indicates that the unequaled cash flow report, firm age, and firm size have no effect on financial performance. This finding is factually contradictory to the theoretical explanation, so it cannot be used as a general reference. However, what … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 3 publications
0
1
0
1
Order By: Relevance
“…Istiyandra and Susila [15] concluded that firm age has a significant influence on financial performance. However, other studies from Sitanggang et al [27] state that the firm age does not have a significant influence on financial performance. H3: Firm age has a positive and significant effect on financial performance.…”
Section: Firm Age and Financial Performancementioning
confidence: 87%
See 1 more Smart Citation
“…Istiyandra and Susila [15] concluded that firm age has a significant influence on financial performance. However, other studies from Sitanggang et al [27] state that the firm age does not have a significant influence on financial performance. H3: Firm age has a positive and significant effect on financial performance.…”
Section: Firm Age and Financial Performancementioning
confidence: 87%
“…This means that companies with a long life but not accompanied by an increase in operations, cause the production of goods will decrease and have an impact on the company's profits. However, Sitanggang et al [27] stated that the age of the company does not have a significant influence on financial performance.…”
Section: Firm Age and Financial Performancementioning
confidence: 99%
“…An information includes a note or description as well as the condition of the company's description. For manufacturing companies, this is done in the form of financial reports that contain all accurate and reliable information about companies and investments that will be useful in supporting successful business development (Sitanggang et al, 2021).…”
Section: Literature Review Signaling Theorymentioning
confidence: 99%
“…These companies usually have a good reputation so they can earn high profit margins when selling goods (Endaryono, Nurhayati, and Setiawati, 2019). According to research from (Melania & Tjahjono, 2022) and (Sitanggang, 2021) says that the older the firm means it does not guarantee that it will always go according to plan in generating profits. The age of the firm will show a lot of experience, but showing a lot of experience does not make the firm generate maximum profits.…”
Section: Introductionmentioning
confidence: 99%